A trustworthy and incentivized smart grid energy trading framework using distributed ledger and smart contracts. (1st June 2021) - Muzumdar, Ajit; Modi, Chirag; G.M., Madhu; Vyjayanthi, C.
Abstract: The smart grid integrated with renewable energy sources (RESs) allows to perform peer to peer selling of energy via Local Energy Market (LEM). However, it faces the challenges of lack of transparency and verification of energy distribution, single-point failure in the energy data management, user's privacy, non-incentivized trading and lack of trust on the energy trading. To address these problems, we propose a trustworthy and incentivized framework for smart grid energy trading using distributed ledger technology and smart contracts. We propose different smart contracts viz ; energy injection into smart grid, energy bidding to submit energy demand, energy trading and energy utilization. These contracts run on an ethereum blockchain platform with proof of stake (PoS) consensus mechanism to record energy trading related data. We have applied an iterative Vickrey–Clarke–Grove (Vickrey auction) method for the incentivized energy trading in context of both prosumers and consumers. The proposed framework offers trustworthy and incentivized trading of energy, participants' privacy, data transparency and no single point failure. The experimental results of the proposed framework are derived in terms of average cost of energy injection and bidding transactions, throughput and the incentivized trading by considering different test scenarios.